PENGARUH LDR, NIM, NPL, BOPO, DAN CAR TERHADAP ROA PADA BANK BUMN YANG TERDAFTAR DI BANK INDONESIA - Tursidi, 08.05.52.0080; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This research has a purpose to analyze the effect on LDR, NIM, NPL,BOPO and CAR for Returm om Asset (ROA) on BUMN the bank in indonesia. ROA shows a comparison between the profit before tax to total assets (total assets). So, important for the banks to will be analyzed the factors to determined ROA targeted match with condition of banking and state of economy This research using data from BUMN published financial reports 2002-2015 period. Analysis technique used is analyzed multiple linear regression and the hypothesis testing with use F and t test. Others also done a classic assumption test covering normality test, multicolinearity test, heteroscedasticity test and autocorrelation test.Â Conclussion from this research describe that statistical result of LDR variable show negative and significant influence towards on ROA, NIM variable show positive and significant towards on ROA, NPL variable show negative and significant towards on ROA. BOPO variable show negative and significant towards on ROA. And CAR variable show positive and significant towards on ROA.Keywords: LDR, NIM, NPL, BOPO, CAR, ROA